1996
DOI: 10.1038/bjc.1996.2
|View full text |Cite
|
Sign up to set email alerts
|

Oestrogen receptor: a stable phenotype in breast cancer

Abstract: Summary Oestrogen receptor (ER) expression in breast cancer is regarded as a phenotype that may change during the natural history of the disease or during endocrine therapy. It has been suggested that in up to 70% of tumours that show acquired resistance the mechanism may be changed in ER status from positive to negative. This paper proposes an alternative hypothesis that ER expression is a stable phenotype in breast cancer. The paper reviews the literature on ER expression during the natural history of breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
63
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(65 citation statements)
references
References 73 publications
(60 reference statements)
2
63
0
Order By: Relevance
“…The partial oestrogen antagonist tamoxifen and the newer pure anti-oestrogens are known to down-regulate the expression of ER and ER-regulated gene-products in human breast carcinomas. 12,13,31 In previous work from this unit we have shown a greater extent of ER downregulation to be associated with better quality and longer duration of clinical response on primary tamoxifen. 15 Given the experimental capacity for EFAs to modulate the structure and function of steroid hormone receptors we wished to examine the effect of GLAÏ©/ÏȘ tamoxifen on the expression of ER in this xenograft model of ERÏ©ve breast cancer.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The partial oestrogen antagonist tamoxifen and the newer pure anti-oestrogens are known to down-regulate the expression of ER and ER-regulated gene-products in human breast carcinomas. 12,13,31 In previous work from this unit we have shown a greater extent of ER downregulation to be associated with better quality and longer duration of clinical response on primary tamoxifen. 15 Given the experimental capacity for EFAs to modulate the structure and function of steroid hormone receptors we wished to examine the effect of GLAÏ©/ÏȘ tamoxifen on the expression of ER in this xenograft model of ERÏ©ve breast cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Tamoxifen and other anti-oestrogens are known to down-regulate ER. [12][13][14] Our own group has also recently shown that a greater extent of ER down-regulation was correlated with better clinical response on primary tamoxifen. 15 EFAs have previously been reported to modulate the structure and function of steroid hormone receptors, including the ER.…”
mentioning
confidence: 97%
“…Hormone ablation therapy, using ER antagonists, are currently a common first-line therapy for ER-positive breast cancers and function by eliciting cell-cycle arrest in hormone-dependant breast cancer cells (Sutherland et al, 1983;Jensen and Jordan, 2003). Although these anti-estrogen therapies are initially effective, B50% of ER-positive patients develop resistance within their lifetime, ultimately leading to therapeutic failure (Encarnacion et al, 1993;Robertson, 1996;Barker, 2003;Ariazi et al, 2006). As such, a significant fraction of patients with ER-positive disease require adjuvant therapies.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 However, the ER expression is gradually lost during tumor progression, leading to a more undifferentiated state. 19 The majority of ER Ï© tumors are diploid, well differentiated, more common in postmenopausal women and less aggressive than ER ÏȘ breast tumors. 15,20 However, the plethora of genes that might be associated with each tumor phenotype remains to be fully explored.…”
mentioning
confidence: 99%